Study the project management software system by identification of the customers needs. The quality function deployment (QFD) application - Tham Chee Siew (2023)
The main objective of our study was to identify the customer's requirements in project management software system. The focus on satisfying the customer's needs places an emphasis on techniques such as Quality Function Deployment (QFD) to help understand those needs and plan a product to provide superior value.